COVID-19: An Update on the Epidemiological, Clinical, Preventive, and Therapeutic Management of 2019 Novel Coronavirus Disease. Issue 1 (January 2021) - Ashraf, Obaid; Virani, Ahmed; Cheema, Tariq
Abstract : The COVID-19 pandemic caused by severe acute respiratory syndrome coronavirus (SARS-CoV-2) remains a serious issue for global health, given widespread infectivity and a high contagion rate. A tremendous amount of data has been generated since it was first identified in December 2019. It is vital to keep up with these data from across the world at a time of uncertainty and continuously evolving guidelines and clinical practice. This review provides an update on recent developments concerning epidemiology, clinical presentation, treatment options, and scientific advancements to combat the COVID-19 pandemic.